Analisis Usability Menggunakan Metode System Usability Scale (Studi Kasus: Aplikasi PeduliLindungi versi 4) - Husaen, Zaka Fadhullah; Widodo, Suryarini (Yayasan Petra Harapan Bangsa, 2022)
The usability level of the PeduliLindung application version 4 used by the Indonesian people during the Covid-19 pandemic until now needs to be measured. One of the Usability measurement tools is the System Usability Scale method. This study aims to measure the Usability level of the PeduliLindung application version 4 in the hands of users. The results of the Usability measurement are expected to be an evaluation material for improving applications in future updates. A total of 50 users of the PeduliLindung version 4 application participated as respondents. The results of the study can describe the Usability level of the PeduliLindung application version 4 from the user's point of view. The average score of the System Usability Scale obtained is 70.8. The average score illustrates that the PeduliLindung version 4 application has a Usability level that is acceptable to the community, but there is no more interest than just using it for yourself.